DAMPAK BLUE ECONOMY TERHADAP EKOSISTEM DI ASIA PASIFIK - Muhammad Andhika Pradana (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2021)
ABSTRACT This research explains the effect of the blue economy on ecosystems in Asia Pacific, particularly the application of the blue economy model. Asia Pacific Economic Cooperation (APEC) is an economic cooperation forum for Asia Pacific countries which aims to improve welfare and economic growth with a competitive and sustainable marine and fisheries perspective for the welfare of society. To realize the vision of marine and fisheries development, a blue economy model is implemented. The method used in this research is to use qualitative research methods, qualitative research is a qualitative approach research method looking at multiple realities (compound), the results of construction in a holistic view. The accuracy of the researchers is very concerned in a qualitative study. Because this study does not use statistical measurements but rather the development of information from respondents and sources of research material, it is expected that the objectivity of the researchers will be more concerned so as not to affect the results of future research. Based on the research results show that the function of APEC is seen from its role to facilitate economic growth. Member countries with the achievement of the blue economy agreement are committed to forming partnerships that are more integrated, sustainable, inclusive and mutually beneficial. Apart from having the potential for fisheries commodities, Indonesia takes advantage of this opportunity to contribute to the implementation phase of the blue economy model in the fisheries industry sector. Keywords: Blue Economy, Asia Pacific Economic Cooperation (APEC), Sustainable Development, Industry, Ecosystems ABSTRAK Penelitian ini menjelaskan tentang Pengaruh Blue Economy terhadap Ekosistem di Asia Pasifik, khususnya penerapan model ekonomi biru. Asia Pacific Economic Cooperation (APEC) merupakan forum kerjasama ekonomi negara-negara Asia Pasifik yang bertujuan untuk meningkatkan kesejahteraan dan pertumbuhan ekonomi yang berwawasan kelautan dan perikanan yang berdaya saing dan berkelanjutan untuk kesejahteraan masyarakat. Untuk mewujudkan visi pembangunan kelautan dan perikanan dilaksanakan model blue economy. Metode yang digunakan dalam penelitian ini adalah dengan menggunakan metode penelitian kualitatif, penelitian kualitatif ialah sebuah metode penelitian pendekatan kualitatif melihat realitas ganda (majemuk), hasil konstruksi dalam pandangan holistik. Ketelitian dari peneliti sangat diperhatikan dalam suatu penelitian kualitatif. Karena pada penelitian ini tidak menggunakan pengukuran secara statistik tetapi lebih ke pengembangan terhadap informasi dari responden dan sumber bahan penelitian, sehingga diharapkan obejktivitas dari peneliti lebih diperhatkan agar tidak mempengaruhi hasil penelitian nantinya .Berdasarkan hasil penelitian menunjukkan bahwa fungsi APEC dilihat dari perannya untuk memfasilitasi pertumbuhan ekonomi negara-negara anggota dengan pencapaian kesepakatan ekonomi biru komitmen untuk membentuk kemitraan yang lebih terintegrasi, berkelanjutan, inklusif dan saling menguntungkan. Selain memiliki potensi komoditas perikanan, Indonesia memanfaatkan peluang tersebut untuk memberikan kontribusi dalam tahap implementasi model ekonomi biru di sektor industri perikanan. Keywords: Blue Economy, Asia Pacific Economic Cooperation (APEC), Pembangunan Berkelanjutan, Industri, Ekosistem.